Life prediction of copper-aluminium composite plate, based on electrical conductivity in a marine atmosphere. (May 2021) - Cheng, Yulin; Zuo, Xiaojiao; Yuan, Xiaoguang; Huang, Hongjun; Zhang, Yifan
Highlights: The corrosion kinetic model under the action of current is obtained. The electrical failure criterion of the material is determined. The life prediction model under energized state is established. A new concept for life prediction of transmission materials is proposed. Abstract: In this paper, the life prediction of copper-aluminium composite plate was investigated by exploiting the conductivity in a marine atmosphere environment. The corrosion kinetic model was established and modified based on the corrosion weight loss under different salt spray concentrations. According to the working standards of conductors, the failure criterion of temperature rises caused by conductive cross-sectional corrosion of composite plate was established. The relationship between salt spray concentration, corrosion time and reduction of the conductive cross-sectional area was provided. The life prediction model of composite plate under conductive conditions was established and verified by experimental and simulation results. The results showed that the failure of the material occurred when the average cross-sectional area of the copper-aluminium composite plate decreased by 37.50% due to corrosion, that is, when the corrosion weight loss was 12.15 g. It was calculated that the service life of the material in an environment with 0.05%, 0.20%, 0.40% and 1.50% salt spray concentration was 13, 128 days, 2539 days, 1311 days and 273 days, respectively.